Effectiveness of an epidermal growth factor-containing cream on postinflammatory hyperpigmentation after 1064-nm Q-switched neodymium-doped yttrium aluminum garnet laser treatment of acquired bilateral nevus of Ota-like macules (Hori's nevus) in Asians: A split-face, double-blinded, randomized controlled study - Penpun Wattanakrai (2022)
Background: Epidermal growth factor (EGF) may promote wound healing and decrease laser-induced postinflammatory hyperpigmentation (PIH). Objectives: To evaluate the effectiveness of an EGF-containing cream on PIH, post-laser erythema, and transepidermal water loss (TEWL) after 1,064-nm Q-Switched Nd: YAG laser treatment of Hori's nevus. Methods: This is a split-face, double-blinded, randomized, controlled study conducted in 30 subjects with bilateral Hori's nevus. After laser treatment, participants were randomized to apply EGF cream on one facial side and placebo on the other side for 8 weeks. The incidence and intensity of PIH were assessed by photographs and melanin indexes (MIs) ratio at baseline, Week 2, Week 4, and Week 8. Post-laser erythema and TEWL were measured at baseline, Day 1, Day 3, and Day 7. Side effects and patient satisfaction score were evaluated. Results: The incidence of PIH was 26.7% in EGF group compared to 20% in placebo. The intensity of PIH was 0.057 (0.033–0.086) and 0.045 (0.027–0.076) in EGF and placebo group, respectively. There was no significant difference in both incidence (p = 0.5) and intensity of PIH (p = 0.145). Post-laser erythema was not statistically different between groups. EGF could alleviate TEWL better than placebo but without statistical significance. Patient satisfaction score was significantly higher in EGF group compared to placebo (p < 0.001). Conclusions: The EGF-containing cream could not prevent PIH. It may reduce laser-induced skin barrier damage. Future studies in more subjects are needed.